Efeito da granulometria na flotação de quartzo - Ana Maria Vieira (2005)
Mineral particles of different sizes are present in flotation slurries. The particles size range varies from of millimetres to micrometers. Industrial practice and several investigations show that the extent of flotation of a certain mineral depends on its size. So, the sizes of the mineral particles present in the slurry becomes, also, an important variable in the sequence of events that lead to the flotation of a particle. In this work theeffect of size in the flotation of quartz was investigated. Pure quartz samples in different size ranges were utilised. Firstly, experiments were performed in a mechanical flotation cell, aiming at achieving the best conditions for high recovery of quartz particles, mainly coarse particles. Next, column flotation experiments were performed, with thetarget of reaching the same level of quartz particles recovery, mainly coarse particles, achieved in the mechanical cell. The results of mechanical cell flotation showed, in general, that the flotation of coarse quartz is possible under favourable flotation conditions, especially pH and collector dosage. Also, the feed consisting of coarse and medium quartz and adequate proportion of fine quartz, favours the flotation of coarse quartz present in this system. The results of zeta potential determination showed a correlation with the flotation results in the mechanical cell, for the pH value in which quartz presents the highest intensity of surface charge is the same yielding the highest recovery of fine, medium and coarse quartz. The results achieved in the flotationcolumn showed that the collector dosage required for high recovery of coarse quartz is higher than required in the mechanical flotation. Nevertheless, the best flotation pH was the same in both cases. The experiments in the column showed also that the presence of different quartz particles sizes in the feed pulp favours the flotation of coarse quartz.